Cellular and molecular atlas of the placenta from a COVID‐19 pregnant woman infected at midgestation highlights the defective impacts on foetal health. Issue 4 (9th February 2022) - Chen, Jingsi; Du, Lili; Wang, Feiyang; Shao, Xuan; Wang, Xiaoyi; Yu, Wenzhe; Bi, Shilei; Chen, Dexiong; Pan, Xingfei; Zeng, Shanshan; Huang, Lijun; Liang, Yingyu; et al.
Abstract: Objectives: The impacts of the current COVID‐19 pandemic on maternal and foetal health are enormous and of serious concern. However, the influence of SARS‐CoV‐2 infection at early‐to‐mid gestation on maternal and foetal health remains unclear. Materials and methods: Here, we report the follow‐up study of a pregnant woman of her whole infective course of SARS‐CoV‐2, from asymptomatic infection at gestational week 20 to mild and then severe illness state, and finally cured at Week 24. Following caesarean section due to incomplete uterine rupture at Week 28, histological examinations on the placenta and foetal tissues as well as single‐cell RNA sequencing (scRNA‐seq) for the placenta were performed. Results: Compared with the gestational age‐matched control placentas, the placenta from this COVID‐19 case exhibited more syncytial knots and lowered expression of syncytiotrophoblast‐related genes. The scRNA‐seq analysis demonstrated impaired trophoblast differentiation, activation of antiviral and inflammatory CD8 T cells, as well as the tight association of increased inflammatory responses in the placenta with complement over‐activation in macrophages. In addition, levels of several inflammatory factors increased in the placenta and foetal blood. Conclusion: These findings illustrate a systematic cellular and molecular signature of placental insufficiency and immune activation at the maternal–foetal interface that may be attributed to SARS‐CoV‐2 infection at the midgestation stage, which highly suggests the extensive care for maternal and foetal outcomes in pregnant women suffering from COVID‐19. Abstract : Here, we report the follow‐up study of a pregnant woman of her whole infective course of SARS‐CoV‐2, from asymptomatic infection at gestational week 20 to mild and then severe illness state, finally cured at Week 24 and delivering at Week 28 due to incomplete uterine rupture. The placenta from this case exhibited more syncytial knots and lowered expressions of syncytiotrophoblast‐related genes. The single‐cell RNA sequencing analysis demonstrated impaired trophoblast differentiation, activation of antiviral and inflammatory CD8 T cells, as well as the tight association of increased inflammatory responses with complement over‐activation in macrophages. These findings illustrate a systematic cellular and molecular signature of placenta insufficiency and immune activation that may be attributed to SARS‐CoV‐2 infection at midgestation stage, which highly suggests the extensive care for maternal and fetal outcomes in COVID‐19 pregnancy.